2021
DOI: 10.2147/ijn.s299261
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Halloysite Nanotubes as a Potential Platform for Oral Modified Delivery of Different BCS Class Drugs: Characterization, Optimization, and Evaluation of Drug Release Kinetics

Abstract: This study systematically investigated the potential of four model drugs (verapamil HCl, flurbiprofen, atenolol, and furosemide), each belonging to a different class of Biopharmaceutics Classification Systems (BCS) to be developed into oral modified release dosage forms after loading with halloysite nanotubes (HNTs). Methods: The drugs were studied for their loading (mass gain %) by varying solvent system, method, pH, and ratios of loading into the nanotubes using D-optimal split-plot design with the help of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…For example in work of Shi et al HNTs covered with 3-amino-propyl-triethoxysilane (APTES) were given as an antisense oligonucleotide to the HeLa cells [148]. Some researches describe the systematic investigations of HNTs to fabricate the oral drug delivery platform on the base of commercially available drugs including resveratrol, paclitaxel, verapamil [132,[149][150][151][152][153][154][155][156]. Recently, Lazzara et al conducted an extensive in vitro toxicity and genotoxicity analysis of hal-loysite nanotubes from various sources in HeLa, CHO and HepG2 cell lines and concluded that halloysite has good biocompatibility at low doses and short exposure times [157].…”
Section: Clay Nanotubes-based Drug Delivery Systemsmentioning
confidence: 99%
“…For example in work of Shi et al HNTs covered with 3-amino-propyl-triethoxysilane (APTES) were given as an antisense oligonucleotide to the HeLa cells [148]. Some researches describe the systematic investigations of HNTs to fabricate the oral drug delivery platform on the base of commercially available drugs including resveratrol, paclitaxel, verapamil [132,[149][150][151][152][153][154][155][156]. Recently, Lazzara et al conducted an extensive in vitro toxicity and genotoxicity analysis of hal-loysite nanotubes from various sources in HeLa, CHO and HepG2 cell lines and concluded that halloysite has good biocompatibility at low doses and short exposure times [157].…”
Section: Clay Nanotubes-based Drug Delivery Systemsmentioning
confidence: 99%
“…The samples were attached to aluminum stubs with double side adhesive carbon tape, gold coated (250 0A JFC-1500 JEOL), and sputter coater. SEM photographs were recorded and examined (Husain et al, 2021).…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…In addition, due to their hollow shape, they can promote encapsulated efficacy and can also help to protect susceptible biological molecules through the host’s delivering tract [ 17 ]. So far, a variety of advantageous applications based on native HNTs has been researched, including biologic nanocarriers [ 18 , 19 , 20 , 21 , 22 ]. Nevertheless, several studies have suggested that functionalized HNTs manufactured by grafting their surfaces with some substances can enhance their desirable characteristics for use in drug delivery systems [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%